The Effect of Content Marketing, Live Shopping, and Flash Sale on Skintific Purchase Decisions on Tiktok Social Media Users - Ardian Dio Fauzi; Rini Adiyani; Kurniawati Darmaningrum (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: This study aims to examine the influence of (1) Content Marketing, (2) Live shopping, and flash sales on purchasing decisions for Skintific products on TikTok. Methodology: This research utilizes a quantitative approach with primary data collected through Likert-scale questionnaires from 100 respondents in Surakarta. Data analysis was conducted using SPSS 26 software with statistical tests, including partial and simultaneous tests, to assess the impact of marketing strategies. Main Findings: Content marketing influences purchasing decisions by 13.6%, live shopping by 20.3%, and flash sales by 22%. The R-square value indicates that these three strategies collectively contribute 55.9% to purchasing decisions, while 44.1% is influenced by other factors not examined in this study. Novelty/Originality of this study: This study provides empirical insights into the effectiveness of TikTok's digital marketing strategies, particularly live shopping and flash sales, in shaping consumer purchasing behavior. It advances existing knowledge by highlighting the significant impact of visual engagement and urgency-driven marketing on millennials and Gen Z consumers within the skincare industry.